The weak link in assistive technology – the internet. (July 2021) - Cunningham, Todd; Lamond, Bronwyn
Highlights: Time to open client-side programs is shorter than server-side programs with low-speed internet. Caching and preloading programs overcomes this challenge. Internet speed has a significant impact on how well assistive technology programs function. Consider internet speed when selecting assistive technology programs for students. Abstract: Assistive Technology (AT) allows individuals with disabilities to circumvent areas of weakness. Many AT tools have been developed for server-side environments with the assumption that students will have access to sufficiently fast internet when they need it in order to use the tools effectively. However, this is not always the case. In the current study, the impacts of client-side versus server-side applications, internet speed, and the cache on the loading time of four popular AT tools were examined. Client-side applications were expected to result in the fastest loading time, and a preloaded cache was expected to eliminate much of the disparity between high- and low-speed internet. These hypotheses were largely confirmed. There were significant differences in the time to open client-side programs compared to server-side programs with low-speed internet. Several classroom implementation strategies for server-side AT are discussed.